Herpes Simplex Virus and Pattern Recognition Receptors: An Arms Race - Zhao, Jun; Qin, Chao; Liu, Yongzhen; Rao, Youliang; Feng, Pinghui (Frontiers in Immunology, 2021)
Herpes simplex viruses (HSVs) are experts in establishing persistent infection in immune-competent humans, in part by successfully evading immune activation through diverse strategies. Upon HSV infection, host deploys pattern recognition receptors (PRRs) to recognize various HSV-associated molecular patterns and mount antiviral innate immune responses. In this review, we describe recent advances in understanding the contributions of cytosolic PRRs to detect HSV and the direct manipulations on these receptors by HSV-encoded viral proteins as countermeasures. The continuous update and summarization of these mechanisms will deepen our understanding on HSV-host interactions in innate immunity for the development of novel antiviral therapies, vaccines and oncolytic viruses.